pharmaceutical-sciences 2020
DOI: 10.36468/pharmaceutical-sciences.649
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol Profile, Antioxidant and Hypoglycemic Activity of Acalypha hispida Leaf Extract

Abstract: This is an open access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 3.0 License, which allows others to remix, tweak, and build upon the work non-commercially, as long as the author is credited and the new creations are licensed under the identical terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…Polyphenols are bioactive compounds that act as free radical scavengers in the body (Gelen et al, 2021). Our study has previously identified the polyphenols content in the Acalypha hispida leaves extract (Alfarisi et al, 2020a). There are 17 types of flavonoids and 5 types of phenolic acid in the A. hispida leaves extract with antihyperglycemic and antioxidant properties (Alfarisi et al, 2020a).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Polyphenols are bioactive compounds that act as free radical scavengers in the body (Gelen et al, 2021). Our study has previously identified the polyphenols content in the Acalypha hispida leaves extract (Alfarisi et al, 2020a). There are 17 types of flavonoids and 5 types of phenolic acid in the A. hispida leaves extract with antihyperglycemic and antioxidant properties (Alfarisi et al, 2020a).…”
Section: Introductionmentioning
confidence: 93%
“…Our study has previously identified the polyphenols content in the Acalypha hispida leaves extract (Alfarisi et al, 2020a). There are 17 types of flavonoids and 5 types of phenolic acid in the A. hispida leaves extract with antihyperglycemic and antioxidant properties (Alfarisi et al, 2020a). However, there are several limitations to using herbal medicines in crude extracts, mainly through oral administration, which are high doses and poor absorption of bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…5 . Ethanol extract of Acalypha hispida shows anti-inflammatory and anti-oxidant activity 7 . Its leaf extract contain phenols found to be active against Rhizopussp, Penicilliumsp, Sclerotiumrolfsii, Fusariumsp and Aspergillus niger 7 .…”
Section: Phyto Constituentsmentioning
confidence: 99%
“…The plant has been reported to have various pharmacological activities such as anti-microbial and cytotoxic activities 8 , anti-oxidant & hypoglycemic 7 , trypanocidal effect 9 , anti-fungal activity 5 , anti-inflammatory 10 , free radical scavenging activities 12 , phytochemical constituents 3 , in-vitro anti-oxidant & anti-inflammatory potential 4 , anti-microbial 6 , toxicity activities etc.…”
Section: Phyto Constituentsmentioning
confidence: 99%
“…For the most part, scholars have focused on studying crude extracts (organic or aqueous), although a small number have also looked at pure substances themselves. It was shown that the vast majority of plant extracts and pure chemicals were effective against either α -amylase or α -glucosidase [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%